The score study procedures of three collegiate wind band conductors - Feyes, Andrew Dean (Kansas State University, 2017)
This study examined the characteristics of the score study processes implemented by three collegiate wind band conductors. Participants engaged in anticipatory discussion, think-aloud score study session, and a follow up interview to verify researcher inference and observation. Using a multiple case study methodology, the research focused on identifying the individual score study process of each conductor and the impact held beliefs and educational influences had on these processes. The research then compared cases to identify common and unique interactions across participants.
Keywords: Score study; Wind band; Conductor